Novel treatment and prophylaxis of uncomplicated urinary tract infections 1 - Naber, Kurt G. (Henry Stewart Talks, 2023)
Clinical definitions of uncomplicated UTI, Analysis and diagnosis of uncomplicated UTI, Acute Cystitis Symptom Score, Antibiotic treatment and antibiotic resistance, Ibuprofen versus fosfomycin for uncomplicated UTI, Ibuprofen versus pivmecillinam for uncomplicated UTI, Efficacy and safety of BNO 1045, Canephron® N for uncomplicated UTIs